There and back again: contributions on Pseudevoplitus Ruckes (Heteroptera: Pentatomidae) - Grazia, Jocelia; Bolze, Gisele Jardim; Barão, Kim Ribeiro (Zootaxa, 2016)
Pseudevoplitus Ruckes was recently revised and new species were described. The genus has a Neotropical distribution, with species mainly found in the Amazon. Here, we describe the previously unknown female of P. roraimensis and add localities to its known distribution. Also, a new species, P. angelomachadoi sp. nov. (Holotype male deposited in MNHN: French Guiana, Acarouany, 15.IX.1998, A. Matocq leg.), from the Amazonia of French Guiana is described; it can be distinguished from other species of the genus mainly by the bell-shaped pygophore in males, and the gonocoxites 8 widely obscuring the laterotergites 8 basally, in females,  a unique character of this species. The key to species of Pseudevoplitus is updated to include the new species and females.